Seroprevalence of Toxoplasmosis in blood donors of Hamadan transfusion center in 2013 - masoume Gholami (Yafteh, 2015)
Background: Toxoplasmosis with a worldwide distribution is one of the most common opportunistic infections in the immunodeficient patients and causes abortion and congenital complications in pregnant women infected with acute infection. The main route of infection is contact with infected cat and consuming under-cooked meat. Because the presence of parasite in the all body fluids, it is probable that transfusion during acute infection leads to transmission of the parasite. The aim of this study was to evaluate the IgM and IgG antibodies in the Hamadan blood donors and its relation to some epidemiologic risk factors. Materials and Methods: In this cross-sectional study, a total of 540 blood specimens were taken randomly from healthy blood donors in the Hamadan blood transfusion center. All samples examined by ELISA method for IgG and IgM antibodies. The results analyzed in relation to epidemiological factors such as age, gender, occupation and some Toxoplasma infection risk factors. Results: About 518 participants in this study were male, others were female. Totally, 294 (54.4%) of studied population were positive for IgG antibody and 10 (1.9%) were positive for IgM antibody. There was no significant relationship between seropositivity and Toxoplasma infection risk factor. Conclusion: Because the screening didn’t perform on the blood donors in Hamadan according to results of this study, Toxoplasma infection in blood donors of Hamadan is relatively high and, the rate of IgM antibody could considered for screening of this population.